Nano-Copper Supplementation Reduces Fecal Copper Excretion and Enhances Piglet Performance Under Heat Stress - Xiarui Xiao; Duo Xu; Haixin Zhang; Qian Xing; Daiwen Chen; Xiangbing Mao; Quyuan Wang; Huifen Wang; Hui Yan (Agriculture)
This study aimed to evaluate the effects of dietary nano-copper supplementation on growth performance, nutrient digestibility, antioxidant status, inflammatory response, and intestinal barrier function in weanling pigs under heat stress conditions. Forty 20-day-old weaned weanling pigs (Yorkshire × Landrace × Duroc) weighing 6.49 ± 0.08 kg were randomly divided into five treatments with eight replicates each. The pre-feeding period was 2 days, followed by a 22-day experimental period. All groups were exposed to high heat conditions at 35 ± 1 °C. The control group received a basal diet, while the low copper sulfate (LC) group received a diet with 50 mg/kg of copper sulfate, the high copper sulfate (HC) group received a diet with 150 mg/kg of copper sulfate, the low nano-copper (LNC) group received a diet with 50 mg/kg of nano-copper oxide, and the high nano-copper (HNC) group received a diet with 150 mg/kg of nano-copper oxide. Compared to the basal group, pigs supplemented with copper (either CuSO4 or nano-CuO) exhibited significantly higher average daily gain (ADG, p < 0.048) and feed intake (ADFI, p = 0.005), with the 50 mg/kg nano-copper group showing improved nutrient digestibility (p < 0.05) and intestinal morphology. Nano-copper supplementation significantly enhanced mucosal SOD activity (p < 0.05), reduced MDA levels (p < 0.05), and downregulated pro-inflammatory cytokines such as IL-1β and IL-6 (p < 0.05). Notably, 50 mg/kg of nano-copper increased the apparent total tract digestibility (ATTD) of copper to 30.29%, significantly higher than the 16.55% observed in the 150 mg/kg CuSO4 group (p < 0.05). Furthermore, fecal copper concentration was significantly reduced by 20.7% in the 50 mg/kg nano-copper group compared to copper sulfate (p < 0.001). In conclusion, nano-copper appears to be a promising alternative to copper sulfate for improving growth performance and reducing fecal copper concentrations in weanling pigs under heat stress conditions.